The Effect of usıng vırtual realıty ın 6th grade scıence course the cell topıc on students’ academıc achıevements and attıtudes towards the course - Sarıoğlu, Serhan; Girgin, Sonmez (Journal of Turkish Science Education, 2020)
Technology is quickly integrated into education in today's conditions and is increasingly used in classroom settings. It is important to ensure that technology adapts to education at the same speed so that it can meet the needs of the era and the students. One of the technologies that is rapidly spreading recently is virtual reality technology. The visual materials created in a three-dimensional environment with virtual reality technology provide the audience with a real-life experience thanks to the content players. These virtual environments can provide the opportunity to observe environments which can be difficult or impossible to observe or dangerous in real life in three dimensions with a realistic detail. In this respect, it is important to ensure that virtual reality technology adapts to science courses. In this study, it was aimed to investigate the effect of virtual reality usage in science teaching on 100 students attending 6th grade in Orhaneli district of Bursa province in 2017-2018 academic year. The study was designed as an experimental model of quantitative research methods. The Cell Knowledge Test developed by the researcher in the experimental and control groups generated by random assignment was applied separately before and after the cell subject was processed. In the experimental group, before and after the use of virtual reality applications which were adapted by the researcher, the attitude levels towards the course and the differences between these levels were revealed with the help of an Attitude Scale towards Science and Technology Course. As a result of the research, it was concluded that the use of virtual reality technology in the cell subject teaching has a significant effect on students' achievement and attitudes towards the course.
Keywords: Virtual Reality; Instructional Technology; Student Attitude